PEMBERIAN GANTI RUGI KEPADA MASYARAKAT UNTUK PENGADAAN TANAH DALAM PEMBANGUNAN JALAN TOL OLEH PEMERINTAH(Studi Kasus Ruas Jalan Tol Padang - Pekanbaru) - Fallen Annisa Aji Putri, (2023)
The right to control land from the state means that the state (government) is not the owner of the land. However, the government has the right to regulate the allotment, use, supply and maintenance of land, regulate legal relations between people and land, and regulate legal actions against land while taking into account the social function of land rights as referred to in Article 6 of the Basic Agrarian Law. However, in land acquisition arrangements, land acquisition for public purposes can be described using the legal basis of Law no. 2 of 2012 does not use Law no. 20 of 1961 concerning Revocation of Rights to Land and Objects on it. Land acquisition is essentially a government action to acquire land for the public interest, based on deliberations to reach an agreement on the transfer of rights and compensation before the rights are revoked. But in reality there are many things that do not represent this theory. However, in reality there are a lot of compensations that are not in accordance with the rules or procedures that have been made and should be carried out. However, in reality many problems occur and are not appropriate. In overcoming the problem of land acquisition, a solution can be proposed. Based on the nature of the dispute, disputes are divided into 2 (two) types, namely: First, state administration disputes. Disputes arise due to the issuance of State Administrative Decrees by state administrative bodies/officials.